Comparison of Students’ Learning Outcomes During the End of the COVID-19 Period and After the COVID-19 Pandemic (2023–2024) - Afriansyah, Hade; Ahmad Sabandi (Global Action and Education for Society, 2025)
This study aims to identify the differences in students’ learning outcomes between the final year of the COVID-19 pandemic and the year following the pandemic. This research employs a quantitative approach, in which the researcher analyzed students’ learning outcomes in numerical form for the courses Educational Administration and Educational Supervision during the January–June 2023 and January–June 2024 semesters. The collected data were processed using descriptive methods, a Normality Test, and a Normalized Gain Test. The results of the study indicate that there are differences in students’ learning outcomes between the one-year period at the end of the COVID-19 pandemic and the one-year period after the pandemic.